The Role of Social Capital in Disaster Management Studies - Andy Arya Maulana Wijaya; Hendra Wijayanto; L.M. Azhar Sa'ban (Universitas Muhammadiyah Ponorogo, 2026)
Recent studies explain that the COVID-19 pandemic has caused a complex situation for government policies. This study aims to see the capabilities of social capital during the pandemic, as an alternative to effective disaster management. This article is written based on qualitative research principles, through literature analysis of 35 articles obtained from the Scopus database on social capital and handling of COVID-19 cases. Furthermore, the analysis was carried out using the VosViewer application (density and overlay visualization) to see the network of interrelated and relevant concepts. Topics related to this explain that disaster management studies recognize that social capital has an important role in understanding community-based disaster management efforts, especially during the COVID-19 pandemic. The research trend leads to a typology of social capital that is similar in each community even though it is in different regions, the findings are also followed by a trend that community social capital actually strengthens and is very persuasive in disaster situations, even quite effectively contributing to the process of dealing with the impact of disasters, especially for community social recovery. This research study contributes to the approach to formulating disaster risk mitigation policies based on community social capital capacity.